2023
DOI: 10.3390/metabo13030443
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals Identification and Bioactive Compounds Estimation of Artemisia Species Grown in Saudia Arabia

Abstract: Artemisia species are very important medicinal plants, particularly in the Middle East and in developing countries. Their products have been used in traditional and medicine contemporary for the treating of infectious ulcers, gangrenous ulcers, inflammations, and malaria. Artemisinin derived from Artemisia species has been used as a drug in many countries for malaria disease treatment. Hence, this study aimed to identify and evaluate the bioactive compounds of three species of Artemisia (Artemisia judaica, Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The species A. fragrans revealed the highest amount of artemisinin, followed by A. annua , A. biennis , A. scoparia , and A. absinthium . Similarly, Salehi et al [ 32 ] reported a wide range of variability in artemisinin content across different species of Artemisia . Various environmental and genetic factors affect the amount of artemisinin in Artemisia species [ 20 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The species A. fragrans revealed the highest amount of artemisinin, followed by A. annua , A. biennis , A. scoparia , and A. absinthium . Similarly, Salehi et al [ 32 ] reported a wide range of variability in artemisinin content across different species of Artemisia . Various environmental and genetic factors affect the amount of artemisinin in Artemisia species [ 20 ].…”
Section: Discussionmentioning
confidence: 94%
“…Salehi et al [ 22 ] reported that A. deserti had 5.13 mg/g DW artemisinin. Salih et al [ 32 ] showed that the leaf extract of A. sieberi , A. Judaica , and A. monosperma had about 3.01, 2.5, and 1.9 mg/g DW of artemisinin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many bioactive compounds associated with plant secondary metabolites were found in the GC/MS analysis of Artemisia species. Some of these newly found phytochemical components show biological action [ 13 ]. Artemisia species are essential medical plants now attracting significant interest due to their bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia species are essential medical plants now attracting significant interest due to their bioactive compounds. The interest in them is primarily driven by their use in cosmetic products, manufacture of essential oils, chemical diversity, and biological functionality [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%